Analisis Pengaruh Harga dan Kualitas Layanan Elektronik terhadap Kepuasan Konsumen pada Pengguna Aplikasi Shopee - Sabda Puta Mediti, Oktavianus Chrisna Murti (Jurnal Ilmu Manajemen, 2020)
The internet could be used as a means of online trading which is why often referred to as e-commerce (electronic commerce). The increasingly positive e-commerce growth in Indonesia has resulted in a shift in people's shopping patterns towards online or online shopping, thus making marketers learn various strategies so that consumers continue to feel satisfaction when shopping using applications, especially Shopee online shop applications. The purpose of this research is to analyze consumer satisfaction as measured by the price and e-service quality. The population in this study are respondents with a minimum age of 15 years who is infinite and has to carry out payment of at least 1 time in the last 6 months Shopee application. The sampling techniques used are non-probability sampling by sampling method i.e. judgmental sampling and obtained as much as 220 respondents. The technique of data collection for this research uses online questionnaire distribution with a Likert scale and the technical analysis of the data used is multiple linear regression. The results of this study show that the price and quality of e-service have a positive and significant influence on customer satisfaction variables in Shopee application users.